Vascular-related biomarkers in psychosis: a systematic review and meta-analysis - Li, Xiaojun; Hu, Shuang; Liu, Pozi (Frontiers in Psychiatry, 2023)
BACKGROUND: While the molecular underpinnings of vascular dysfunction in psychosis are under active investigation, their implications remain unclear due to inconsistent and sometimes sparse observations. We conducted a comprehensive meta-analysis to critically assess the alterations of vascular-related molecules in the cerebrospinal fluid (CSF) and blood of patients with psychotic disorders compared with healthy individuals. METHODS: Databases were searched from inception to February 23, 2023. Meta-analyses were performed using a random-effects model. Meta-regression and subgroup analyses were conducted to assess the effects of clinical correlates.RESULTS: We identified 93 eligible studies with 30 biomarkers investigated in the CSF and/or blood.Among the biomarkers examined, psychotic disorders were associated with elevated CSF-to-serum albumin ratio (standardized mean difference [SMD], 0.69; 95% confidence interval [CI], 0.35-1.02); blood S100B (SMD, 0.88; 95% CI, 0.59-1.17), matrix metalloproteinase-9 (MMP-9; SMD, 0.66; 95% CI, 0.46-0.86), and zonulin (SMD, 1.17; 95% CI, 0.04-2.30). The blood levels of S100B, MMP-9, nerve growth factor (NGF), vascular endothelial growth factor (VEGF), intercellular adhesion molecule 1 (ICAM-1) and vascular adhesion molecule 1 (VCAM-1) were altered in patient subgroups differing in demographic and clinical characteristics. Blood S100B level was positively correlated with age and duration of illness. Substantial between-study heterogeneity was observed in most molecules.The alterations in certain vascular-related fluid markers in psychotic disorders suggest disturbances in normal vascular structures and functions. However, not all molecules examined displayed clear evidence of changes. While potential impacts of clinical factors, including the administered treatment, were identified, the exploration remained limited. Further studies are needed to investigate the diverse patterns of expression, and understand how these abnormalities reflect the pathophysiology of psychosis and the impact of clinical factors.